Neuronanomedicine: An Up-to-Date Overview - Daniel Mihai Teleanu; Cristina Chircov; Alexandru Mihai Grumezescu; Raluca Ioana Teleanu (MDPI AG, 2019)
The field of neuronanomedicine has recently emerged as the bridge between neurological sciences and nanotechnology. The possibilities of this novel perspective are promising for the diagnosis and treatment strategies of severe central nervous system disorders. Therefore, the development of nano-vehicles capable of permeating the blood⁻brain barrier (BBB) and reaching the brain parenchyma may lead to breakthrough therapies that could improve life expectancy and quality of the patients diagnosed with brain disorders. The aim of this review is to summarize the recently developed organic, inorganic, and biological nanocarriers that could be used for the delivery of imaging and therapeutic agents to the brain, as well as the latest studies on the use of nanomaterials in brain cancer, neurodegenerative diseases, and stroke. Additionally, the main challenges and limitations associated with the use of these nanocarriers are briefly presented.